A high-dose inoculum size results in persistent viral infection and arthritis in mice infected with chikungunya virus. - Yue Zhang; Hu Yan; Xian Li; Dihan Zhou; Maohua Zhong; Jingyi Yang; Bali Zhao; Xuxu Fan; Jun Fan; Jiayi Shu; Mengji Lu; Xia Jin; et al. (Public Library of Science (PLoS), 2022)
Chikungunya virus (CHIKV) is an emerging mosquito-transmitted alphavirus that leads to acute fever and chronic debilitating polyarthralgia. To date, the mechanism underlying chronic recurrent arthralgia is unknown. In the present study, newborn wild-type C57BL/6 mice were infected with CHIKV, and the virological and pathological features of CHIKV infection were analyzed over a period of 50 days. Acute viral infection was readily established by footpad inoculation of CHIKV at doses ranging from 10 plaque forming unit (PFU) to 106 PFU, during which inoculation dose-dependent viral RNA and skeletal muscle damage were detected in the foot tissues. However, persistent CHIKV was observed only when the mice were infected with a high dose of 106 PFU of CHIKV, in which low copy numbers (103-104) of viral positive strand RNA were continuously detectable in the feet from 29 to 50 dpi, along with a low level and progressive reduction in virus-specific CD8+ T cell responses. In contrast, viral negative strand RNA was detected at 50 dpi but not at 29 dpi and was accompanied by significant local skeletal muscle damage at 50 dpi when mild synovial hyperplasia appeared in the foot joints, although the damage was briefly repaired at 29 dpi. These results demonstrated that a high viral inoculation dose leads to viral persistence and progression to chronic tissue damage after recovery from acute infection. Taken together, these results provide a useful tool for elucidating the pathogenesis of persistent CHIKV infection and viral relapse-associated chronic arthritis.